Pengaruh Work Family Conflict dan Budaya Organisasi Terhadap Komitmen Organisasi Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Wardana, I Wayan Adhitya Kusuma; Mahyuni, Luh Putu (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research was carried out with the aim of investigating the role of work family conflict and organizational culture on job satisfaction as mediators and organizational commitment. This study was carried out by taking locations in Rama Krisna Tuban with a target population including all employees who work for the organization. By determining a saturated sample, the entire population was used, namely 160 employees who participated as research respondents. Empirical data was collected through distributing questionnaires with a 10-point Likert Scale and then analyzed using the Structural Equation Modelling approach with SmartPLS. Research findings have succeeded in proving that work demands as well as family demands can significantly reduce job satisfaction and employee commitment to the organization. Furthermore, the research results confirmed that a good work culture is believed to be able to increase job satisfaction and organizational commitment. Interesting findings in this research show that job satisfaction can act as a mediating variable in the relationship between constructs. This research is able to make a positive contribution to human resource management literature and practically for Rama Krisna Tuban in increasing job satisfaction and employee commitment to the organization